Association Between Telecommuting Environment and Low Back Pain Among Japanese Telecommuting Workers: A Cross-Sectional Study. Issue 12 (14th December 2021) - Matsugaki, Ryutaro; Muramatsu, Keiji; Tateishi, Seiichiro; Nagata, Tomohisa; Tsuji, Mayumi; Hino, Ayako; Ikegami, Kazunori; Fujino, Yoshihisa; Matsuda, Shinya
Abstract : Objectives: We evaluated the relationship between telecommuting environment and low back pain (LBP) among desk-based workers in Japan. Methods: This cross-sectional study included 3663 desk-based, telecommuting workers. LBP was assessed using a 0 to 10 numerical rating scale. The telecommuting environment was evaluated using subjective questions. Mixed-effects logistic regression analysis was used to evaluate this association. Results: The results of mixed-effects logistic model revealed that not having a place or room to concentrate on work, desk not well-lit enough for work, lack of space on the desk to work, not having enough legroom, and uncomfortable temperature and humidity conditions in the workspace were significantly associated with higher odds of LBP. Conclusions: Our findings suggest that telecommuting environment is associated with the prevalence of LBP.